Understanding political−economic development in the American South. (24th September 2019) - Krause, George A.; Zarit, Matthew
Abstract: We propose an empirical strategy to adjudicate between competing explanations of political–economic development in the American South. This strategy evaluates the dynamic relationship between partisan control of representative institutions and economic performance, both before and after major partisan realignment forces and economic conditions had structurally transformed the American South. The political–economic development of low‐capacity Southern states since the early 1980s reflects a "virtuous cycle" of rising income growth and partisan balance of state legislatures mutually reinforcing one another. These findings reconcile conflicting claims regarding the catalytic nature of political–economic development coevolution in the American South and have broader implications for the study of comparative political–economic development.